Research methods laboratory manual for psychology - Langston, William (Thomson Wadsworth, 2005)
William Langston brings the research methods lab right to the student! Now in its Second Edition, his RESEARCH METHODS LABORATORY MANUAL FOR PSYCHOLOGY sustains its well-earned reputation as an innovative, one-of-a-kind solution for research methods classes. Experiments found within the text and on the CD-ROM cover such topics as the Stroop Effect, gender pronouns, and mood and perception-allowing students to experience research methods hands-on while focusing them on the asking and answering of interesting questions, rather than on the actual tracking down of materials. This lab manual will enrich the learning and interest of any lab class